Imitated conduit wick, preparation method and ultrathin vapor chamber
By designing a conduit-like liquid absorbent wick with large and small channels staggered and forming a hairy micro-nano structure on the surface, the problem of reduced heat transfer performance caused by the reduction in the thickness of the liquid absorbent wick has been solved, and more efficient liquid transmission and ultra-high performance have been achieved. The heat transfer performance of thin vapor chambers is improved.
Patent Information
- Application Number
- CN202411732302.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-21
AI Technical Summary
When the existing liquid absorbent core meets the heat dissipation needs of lightweight and high-performance electronic equipment, the heat transfer performance is caused by the reduction of the internal circulating working fluid flow rate caused by the reduction of the thickness of the liquid absorbent core.
Design a catheter-like liquid-absorbing wick, which adopts a staggered layout of large channels and small channels. The surface is equipped with hair-like micro-nano structures, and the liquid transmission performance is enhanced through side holes. The liquid-absorbent core is prepared by blending fine copper powder and iron powder through high-frequency vibration mold filling and sintering, and then undergoes oxidation and reduction treatments to form hairy micro-nano structures.
By increasing the contact area with the liquid working fluid and lateral suction of the condensed liquid working fluid, the imitation conduit liquid absorbing wick improves the capillary performance and liquid transmission efficiency, and improves the heat transfer performance and ultimate power of the ultra-thin vapor chamber.
Smart Images

Figure CN119334174A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of liquid absorbent cores, and in particular relates to a catheter-imitation liquid absorbent core, a preparation method and an ultra-thin heat spreader. Background Art
[0002] With the gradual implementation of applications such as 5G and artificial intelligence technologies, electronic devices such as mobile phones, tablets, and notebooks are constantly developing towards high performance and thinness. Under the demand for high performance, the chip processing capabilities of components are getting stronger and stronger, and the heat dissipation requirements are also getting higher and higher; and the demand for thinness and lightness requires the continuous reduction of the thickness and size of internal components. The heat spreader, as a heat dissipation component, also needs to be reduced in size and the thickness of the internal wick. However, the heat spreader is a phase change heat transfer component, which requires the internal wick to circulate the flow of the internal working fluid. The reduction in the thickness of the wick will reduce the flow of the internal circulating working fluid, which will lead to a decrease in the heat transfer performance of the heat spreader.
[0003] The existing types of wicks mainly include sintered copper powder, flat wire mesh, groove, woven mesh, etc., but they are gradually unable to meet the heat dissipation needs of the continued rapid development of lightweight and high-performance electronic devices. Therefore, it is necessary to develop a wick structure with stronger liquid transmission performance. Summary of the invention
[0004] The main purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a catheter-like liquid-absorbing core, a preparation method and an ultra-thin heat-absorbing plate.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A catheter-like liquid-absorbing core comprises a plurality of tubular microchannels connected to each other at the sides, and the tubular microchannels are provided with through lateral pores;
[0007] Multiple tubular microchannels are arranged in a staggered arrangement of large channels and small channels;
[0008] The surface of the catheter-like liquid-absorbing core is provided with a hair-like micro-nano structure;
[0009] The shape of a single tubular microchannel is one of circular, hexagonal, square and elliptical;
[0010] The shape of the lateral pores is one or more of circular, oval and elongated.
[0011] Preferably, the equivalent diameter of the tubular microchannel of the large channel is 200 to 350 μm; and the equivalent diameter of the tubular microchannel of the small channel is 50 to 100 μm.
[0012] Preferably, the diameter of the lateral pores is 20 to 30 μm, and the distance between the pores is 300 to 1000 μm.
[0013] The present invention also includes a method for preparing a catheter-like absorbent core, which is used to prepare the catheter-like absorbent core provided by the present invention, comprising the following steps:
[0014] S1, powder filling, mixing fine copper powder and iron powder and putting them into a pre-designed mold cavity, vibrating the mold at high frequency to make the powder fully fill the mold cavity, and squeezing the mold to compact the powder;
[0015] S2, sintering, placing the mold filled with powder into a high-temperature furnace, passing a protective gas mixed with nitrogen and hydrogen, and controlling the temperature of the high-temperature furnace at 900°C to 940°C. Under high temperature, the contact surface of the material particles undergoes physical and chemical changes and combines with each other, the fine copper powder forms a tubular microchannel, and the iron powder forms a side pore profile;
[0016] S3, demoulding, demoulding after cooling, and taking out the catheter-like liquid-absorbing core from the mold;
[0017] S4, solution soaking, put the wick into dilute hydrochloric acid to dissolve the iron powder to form lateral pores;
[0018] S5, oxidation, placing the liquid absorbent core into an oxidation furnace for oxidation treatment, the temperature of the oxidation furnace is controlled at 500°C, the oxidant reacts with the liquid absorbent core at high temperature to produce a hairy micro-nano structure on the surface;
[0019] S6. Reduction: placing the wick into a reduction furnace for reduction treatment. The temperature of the reduction furnace is controlled at 400° C. to convert the hairy micro-nano structure obtained by oxidation into a more stable compound.
[0020] The present invention also includes another method for preparing the catheter-like absorbent core, which is used to prepare the catheter-like absorbent core provided by the present invention, comprising the following steps:
[0021] S1, powder filling, mixing fine copper powder with high temperature decomposable powder and putting them into a pre-designed mold cavity, vibrating the mold at high frequency to make the powder fully fill the mold cavity, and squeezing the mold to compact the powder;
[0022] S2, sintering, placing the mold filled with powder into a high-temperature furnace, the temperature of the high-temperature furnace is controlled at 900℃ to 940℃, at high temperature, the contact surface of the material particles undergoes physical and chemical changes and combines with each other, the fine copper powder forms a tubular microchannel, the high-temperature decomposable powder evaporates and disappears after heating and forms a side pore profile;
[0023] S3, demoulding, demoulding after cooling, and taking out the catheter-like liquid-absorbing core from the mold;
[0024] S4, oxidation, placing the liquid absorbent core into an oxidation furnace for oxidation treatment, the temperature of the oxidation furnace is controlled at 500°C, and the oxidant reacts with the liquid absorbent core at high temperature to produce a hairy micro-nano structure on the surface;
[0025] S5. Reduction: placing the wick into a reduction furnace for reduction treatment. The temperature of the reduction furnace is controlled at 400° C. to convert the hairy micro-nano structure obtained by oxidation into a more stable compound.
[0026] The present invention also includes an ultra-thin heat spreader, comprising an upper shell, a lower shell, and a plurality of catheter-like liquid-absorbing cores provided by the present invention;
[0027] The top surfaces of the multiple catheter-like liquid-absorbing cores are connected to the upper shell, and the bottom surfaces are connected to a single-layer catheter-like liquid-absorbing core; the bottom surface of the single-layer catheter-like liquid-absorbing core is connected to the lower shell;
[0028] Intervals are arranged between the plurality of imitation catheter liquid-absorbing cores to form steam channels.
[0029] Preferably, the spacing between the catheter-like wicks is 1.5 mm to 4 mm.
[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0031] 1. The catheter-like liquid absorbent core of the present invention is composed of a plurality of tubular microchannels with a plurality of side holes distributed on the sides, which are arranged and connected. The tubular microchannels can increase the contact area with the liquid medium during longitudinal transmission, thereby improving the capillary performance of the liquid absorbent core; and the side holes can laterally absorb the liquid medium condensed in the ultra-thin heat spreader, and the absorbed liquid medium will continue to be longitudinally transmitted along the tubular microchannels, accelerating the efficiency of the gas-liquid phase change and improving the heat transfer performance of the ultra-thin heat spreader.
[0032] 2. The catheter-like absorbent core of the present invention has a tubular microchannel that adopts a staggered layout of large channels and small channels, which can achieve a larger capillary pressure and a higher permeability, thereby obtaining a better capillary performance, so that the absorbent core can transmit more liquids faster.
[0033] 3. The spacing design of the catheter-like liquid-absorbing core of the present invention can reduce the steam resistance and increase the ultimate power of the heat sink.
[0034] 4. The heat spreader of the present invention is provided with a single-layer duct-like liquid absorption core to achieve the transmission of more liquid to the evaporation end position, which can prevent the temperature of the heat source at the bottom of the evaporation end from being too high and drying up the liquid working medium. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic diagram of the catheter-like liquid-absorbing core;
[0036] Figure 2 is a schematic diagram of a tubular microchannel;
[0037] Figure 3 It is a partial enlarged schematic diagram of the upper surface of the imitation catheter liquid-absorbing core;
[0038] Figure 4is a schematic diagram of an ultra-thin vapor chamber of an embodiment;
[0039] Figure 5 is a cross-sectional view of an ultra-thin vapor chamber of an embodiment;
[0040] Figure 6 is a process flow chart of the preparation method of Example 3;
[0041] Figure 7 is a process flow chart of the preparation method of Example 4;
[0042] Figure 8 It is a schematic diagram of the mold structure for preparing the catheter-like liquid-absorbing core;
[0043] Fig. 9 The figure is a schematic diagram of a mold assembly for preparing a catheter-like liquid-absorbing core;
[0044] Fig.10 It is a schematic diagram of demoulding in the preparation method of the embodiment;
[0045] Fig.11 It is the micro-nano structure produced after the wick is oxidized in the embodiment;
[0046] Explanation of the accompanying drawings: 1- tubular microchannel; 2- lateral pores; 3- upper shell; 4- simulated ductal wick; 5- single-layer simulated ductal wick; 6- lower shell; 7- small channel; 8- large channel; 9- steam channel; 10- droplet; 11- mold cavity; 12- mold; 13- high temperature furnace; 14- dilute hydrochloric acid; 15- oxidation furnace; 16- reduction furnace. DETAILED DESCRIPTION
[0047] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0048] Bamboo grows rapidly, and the water in the growth process is mainly transported through the xylem vessels. In order to quickly transport water from the bottom root system to the dense leaves at the top for transpiration and heat dissipation, the xylem vessel structure in the bamboo stalk has an efficient water transmission capacity. In addition, unlike the solid structure of ordinary tree trunks, the internodes of bamboo are hollow, that is, the cross-sectional area in the bamboo stalk for transporting water is much less than that of ordinary solid tree trunks, so the unit vessel structure of the bamboo stalk has efficient water transmission performance. There are many slender vessels inside the bamboo stalk, which effectively attract and transport liquids through capillary action. In addition, the cell wall of bamboo is porous and can store liquid, further enhancing its liquid absorption capacity. The biological structure of bamboo has been naturally selected to optimize its water absorption and liquid conduction functions, so that it can efficiently absorb water from the soil during its growth. At the same time, the light weight and high strength characteristics of bamboo make it difficult to deform during liquid conduction, maintaining good vessel performance. These factors work together to make the bamboo stalk perform well in liquid absorption and liquid conduction. The present invention refers to the biological structure of bamboo stalks and designs a catheter-like liquid absorption core.
[0049] Example 1
[0050] like Figure 1 , Figure 2 and Figure 3 As shown, a catheter-like absorbent core comprises a plurality of tubular microchannels 1 interconnected at the sides, and the tubular microchannels are provided with through lateral pores 2; the plurality of tubular microchannels are arranged in a staggered arrangement of large channels 8 and small channels 7; and the surface of the catheter-like absorbent core is provided with a hairy micro-nano structure.
[0051] In this embodiment, the shape of the tubular microchannel is one of circular, hexagonal, square and elliptical.
[0052] In this embodiment, the equivalent diameter of the tubular microchannel of the large channel is 200 to 350 μm; the equivalent diameter of the tubular microchannel of the small channel is 50 to 100 μm.
[0053] In this embodiment, the shape of the side pores is one or more of a circular shape, an elliptical shape and a long strip shape, the diameter of the side pores is 20 to 30 μm, and the pore spacing is 300 to 1000 μm.
[0054] The capillary pressure and permeability of the wick are two contradictory coefficients. The small channel has a smaller effective diameter and can provide a larger capillary pressure, but its permeability is smaller; the large channel has a larger effective diameter and a higher permeability, but its capillary pressure is smaller. Capillary pressure is caused by the interaction between liquid and solid (such as surface tension and wettability) and the interaction within the liquid. When liquid enters a tiny pore or channel, the attraction between liquid molecules and the attraction between liquid and solid surface work together to form the phenomenon of liquid rising or flowing. The design of the small channel increases the contact area between the liquid and the solid surface when it flows, thereby enhancing the capillary pressure.
[0055] Porosity calculation formula:
[0056]
[0057] Among them, V holes is the total volume of the through-holes in the porous material, V porous is the total volume of the porous material;
[0058] According to the porosity calculation formula, the larger the through-hole volume, the higher the porosity of the absorbent core will be. Designing large channels can improve the porosity of the absorbent core to a certain extent.
[0059] Permeability is one of the important parameters of the wick, which is related to factors such as the pore size, pore distribution and curvature of the wick. The Kozeny-Carman equation can be used to solve the permeability of porous materials:
[0060]
[0061] For sintered copper powder, the greater the porosity of the wick, the greater its permeability K will be.
[0062] According to Darcy's law, the pressure drop of liquid flow in a porous material is:
[0063]
[0064] Among them, μ l is the liquid viscosity, m is the liquid mass, L is the liquid flow path length, K is the permeability, ρ l is the liquid density, ε is the porosity, A wick is the flow cross-sectional area.
[0065] Porosity and permeability are two important factors that affect the pressure drop of liquid flow. The pressure drop of liquid flow in porous materials is negatively correlated with permeability and porosity. That is, with the increase of porosity and permeability, the pressure drop of liquid flow in the wick will decrease accordingly. The reduction of liquid flow pressure drop resistance is conducive to the flow of liquid working fluid in the wick, thereby improving the heat transfer capacity of the ultra-thin heat spreader.
[0066] In summary, the design of large channels can increase the porosity of the wick and thus increase the permeability. As the porosity and permeability increase, the pressure drop of liquid flow in the wick will decrease, thereby improving the heat transfer capacity of the ultra-thin heat spreader.
[0067] In this embodiment, the structural design of staggered arrangement of large and small channels can achieve greater capillary pressure and higher permeability, thereby obtaining better capillary performance, so that the wick can transmit more liquid faster.
[0068] Example 2
[0069] like Figure 4 As shown, this embodiment provides an ultra-thin heat spreader, comprising an upper shell 3, a lower shell 6, and a plurality of catheter-like liquid-absorbing cores 4 described in Embodiment 1;
[0070] The top surfaces of the multiple simulated catheter absorbent cores are connected to the upper shell, and the bottom surfaces are connected to a single-layer simulated catheter absorbent core 5; the bottom surface of the single-layer simulated catheter absorbent core is connected to the lower shell.
[0071] like Figure 5 As shown, in this embodiment, a plurality of catheter-like wicks are spaced apart to form a steam channel 9, and the size of the space is 1.5 mm to 4 mm.
[0072] like Figure 5 As shown, in this embodiment, the side pores can help the interval-arranged simulated catheter wick to laterally absorb the droplets 10 retained in the steam channel. The laterally absorbed droplets can enter the tubular microchannel and be longitudinally transported by the tubular microchannel to perform the next gas-liquid phase change cycle.
[0073] When the ultra-thin heat spreader is working, the steam condenses on the inner wall of the upper shell to form droplets. The condensation and flow of the liquid in the ultra-thin heat spreader can be divided into three situations: (1) some droplets that are very close to each other merge into large droplets during the growth process; (2) when the droplets increase in thickness and come into contact with the single-layer simulated conduit absorbent core at the bottom of the evaporation end, they are quickly sucked into the side pores and reflux to the evaporation end of the heat pipe under capillary action; (3) small droplets slowly grow larger as the steam continues to condense and aggregate.
[0074] When the steam condensed on the inner wall of the upper shell forms large droplets, if it cannot be quickly adsorbed by the liquid wick, the droplets will grow larger and connect to the upper and lower walls, blocking the steam channel and seriously hindering the flow of steam, resulting in poor heat transfer performance of the ultra-thin heat spreader. For ultra-thin heat spreaders, although a high liquid filling rate can prevent the heat spreader from drying out at higher power and increase the ultimate transmission power of the heat pipe, excessive liquid at the condensation end will connect the upper and lower walls, resulting in a significant reduction in the flow space for steam, thereby causing the heat transfer performance of the heat spreader to decrease. The thinner the inner cavity of the ultra-thin heat spreader, the greater the impact of the liquid filling rate on its heat transfer performance, and excessive liquid filling rates should be avoided as much as possible. Therefore, the design of the side holes can effectively reduce the liquid filling rate of the ultra-thin heat spreader and improve its heat transfer performance by sucking the droplets condensed on the wall back to the liquid wick.
[0075] After the liquid working medium is condensed at the condensing end, it will be transported to the evaporating end through the tubular microchannel of the simulated catheter wick. However, since the bottom of the evaporating end is in contact with the heat source, the high temperature of the heat source can easily dry up the liquid working medium that flows back to the evaporating end. Therefore, this embodiment provides a single-layer simulated catheter wick to achieve the goal of transferring more liquid to the evaporating end, thereby preventing the temperature of the heat source at the bottom of the evaporating end from being too high and drying up the liquid working medium.
[0076] This embodiment applies the catheter-like wick to the ultra-thin vapor chamber structure, which can play the role of a support column and further simplify the structure of the ultra-thin vapor chamber; the thickness of the ultra-thin vapor chamber steam channel is increased through the spacing design and support of the wick, reducing the steam flow resistance, thereby increasing the ultimate heat transfer power of the ultra-thin vapor chamber. The structural design of the steam channel allows the droplets to condense on the upper cover plate and be sucked laterally through the side holes of the wick. Compared with the traditional upper and lower layered structure, this spacing design method not only provides the function of reflux liquid, but also plays the role of supporting the upper and lower cover plates, reducing the use of traditional support columns.
[0077] Example 3
[0078] like Figure 6 As shown, this embodiment provides a method for preparing a catheter-like absorbent core, which is used to prepare the catheter-like absorbent core described in Example 1, comprising the following steps:
[0079] S1, powder filling, mixing fine copper powder and iron powder and putting them into a pre-designed mold cavity 11 arranged with many thin tubular vertical bars, and vibrating the high-frequency vibration mold 12 to fully fill the mold cavity with metal powder; splicing the two parts of the mold along the mold combination surface and placing them perpendicular to the horizontal plane, and then extruding to compact the powder; Figure 8 and Fig. 9 Shown are a schematic diagram of the mold structure and a schematic diagram of the mold combination.
[0080] S2, sintering, placing the mold filled with powder into a high temperature furnace 13, introducing a protective gas mixed with nitrogen and hydrogen, and controlling the temperature of the high temperature furnace to be between 900°C and 940°C (at 940°C, the surface of the copper powder will be slightly melted, but the surface of the iron powder will not be slightly melted). At high temperature, the contact surface of the particles of the material will undergo physical and chemical changes and combine with each other, the fine copper powder will form a tubular microchannel, and the iron powder will form a side pore profile;
[0081] S3, demoulding, cooling down and demoulding, taking out the catheter-like liquid-absorbing core from the mold, Fig.10 As shown;
[0082] S4, solution soaking, placing the wick in dilute hydrochloric acid 14 to dissolve the iron powder to form lateral pores; after the iron powder is completely dissolved, rinse the wick;
[0083] During operation, choose strong acid solutions such as dilute hydrochloric acid and dilute sulfuric acid. It is not advisable to choose acetic acid and oxalic acid solutions; acetic acid is a weak acid. Although it can dissolve iron, its reaction rate is slow, and copper may react slowly in weak acids; oxalic acid is relatively strong and can dissolve iron, but in some cases, copper may also be affected. When choosing hydrochloric acid of appropriate concentration to dissolve iron powder, it is more appropriate to use dilute hydrochloric acid with a concentration between 1M and 2M. 1M to 2M dilute hydrochloric acid can effectively react with iron powder while controlling the reaction rate to avoid violent reactions. Concentrated hydrochloric acid (such as 10M or higher concentrations) reacts violently and may cause a large amount of gas to be released rapidly, increasing safety risks. In addition, higher concentrations of hydrochloric acid may cause a passivation film to form on the surface of iron, affecting subsequent reactions.
[0084] S5, oxidation, the liquid absorbent core is placed in an oxidation furnace 15 for oxidation treatment, the temperature of the oxidation furnace is controlled at 500°C, the oxidant reacts with the liquid absorbent core at high temperature to produce a hairy micro-nano structure on the surface, such as Fig.11 As shown, the micro-nano structure can enhance the hydrophilicity of the liquid, thereby further improving the capillary performance of the liquid absorbent core and transmitting the liquid faster; after the reaction is completed, the liquid absorbent core in the furnace is gradually cooled to prevent damage to the liquid absorbent core caused by sudden temperature changes;
[0085] S6, reduction, placing the wick into a reduction furnace 16 for reduction treatment, the temperature of the reduction furnace being controlled at 400° C., so that the hairy micro-nano structure obtained by oxidation is converted into a more stable compound.
[0086] In addition, in step S1, an integrated mold with multiple spaced-apart imitation catheter wicks and a single-layer imitation catheter wick connected to the bottom can be pre-designed to achieve one-time sintering of multiple imitation catheter wicks and a single-layer imitation catheter wick connected to the bottom, so as to prepare the ultra-thin heat spreader described in Example 2.
[0087] Example 4
[0088] like Figure 7 As shown, this embodiment provides a method for preparing a catheter-like absorbent core, which is used to prepare the catheter-like absorbent core described in Example 1, comprising the following steps:
[0089] S1, powder filling, putting the mixed fine copper powder and high temperature decomposable powder into a pre-designed mold cavity with many thin tubular vertical bars, and vibrating the mold with high frequency vibration to make the metal powder fully fill the mold cavity; splicing the two parts of the mold along the mold combination surface and placing them perpendicular to the horizontal plane, and then extruding to compact the powder;
[0090] S2, sintering, putting the mold filled with powder into a high temperature furnace, the temperature of the high temperature furnace is controlled at 900℃ to 940℃, at high temperature, the contact surface of the material particles will undergo physical and chemical changes and combine with each other, the fine copper powder forms a tubular microchannel, the high temperature decomposable powder evaporates and disappears after heating and forms a side pore profile;
[0091] S3, demoulding, demoulding after cooling, and taking out the catheter-like liquid-absorbing core from the mold;
[0092] S4, oxidation, placing the liquid absorbent core into an oxidation furnace for oxidation treatment, the temperature of the oxidation furnace is controlled at 500°C, and the oxidant reacts with the liquid absorbent core at high temperature to produce a hairy micro-nano structure on the surface;
[0093] S5. Reduction: placing the wick into a reduction furnace for reduction treatment. The temperature of the reduction furnace is controlled at 400° C. to convert the hairy micro-nano structure obtained by oxidation into a more stable compound.
[0094] Similarly, in step S1, an integrated mold with multiple spaced-apart imitation catheter wicks and a single-layer imitation catheter wick connected to the bottom can be pre-designed to sinter multiple imitation catheter wicks and a single-layer imitation catheter wick connected to the bottom in one sintering process, so as to prepare the ultra-thin heat spreader described in Example 2.
[0095] It should also be noted that in this specification, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprises a ..." does not exclude the presence of other identical elements in the process, method, article or device including the element.
[0096] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A catheter-like liquid-absorbing core, characterized in that: It comprises a plurality of tubular microchannels which are interconnected at the sides, and the tubular microchannels are provided with through lateral pores; Multiple tubular microchannels are arranged in a staggered arrangement of large channels and small channels; The surface of the catheter-like liquid-absorbing core is provided with a hair-like micro-nano structure; The shape of a single tubular microchannel is one of circular, hexagonal, square and elliptical; The shape of the lateral pores is one or more of circular, oval and elongated.
2. The catheter-like absorbent core according to claim 1, characterized in that: The equivalent diameter of the tubular microchannel of the large channel is 200 to 350 μm; the equivalent diameter of the tubular microchannel of the small channel is 50 to 100 μm.
3. The catheter-like absorbent core according to claim 1, characterized in that: The lateral pores have a diameter of 20 to 30 μm and a pore spacing of 300 to 1000 μm.
4. A method for preparing a catheter-like absorbent core, used for preparing the catheter-like absorbent core according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, powder filling, mixing fine copper powder and iron powder and putting them into a pre-designed mold cavity, vibrating the mold at high frequency to make the powder fully fill the mold cavity, and squeezing the mold to compact the powder; S2, sintering, placing the mold filled with powder into a high-temperature furnace, passing a protective gas mixed with nitrogen and hydrogen, and controlling the temperature of the high-temperature furnace at 900°C to 940°C. Under high temperature, the contact surface of the material particles undergoes physical and chemical changes and combines with each other, the fine copper powder forms a tubular microchannel, and the iron powder forms a side pore profile; S3, demoulding, demoulding after cooling, and taking out the catheter-like liquid-absorbing core from the mold; S4, solution soaking, put the wick into dilute hydrochloric acid to dissolve the iron powder to form lateral pores; S5, oxidation, placing the liquid absorbent core into an oxidation furnace for oxidation treatment, the temperature of the oxidation furnace is controlled at 500°C, the oxidant reacts with the liquid absorbent core at high temperature to produce a hairy micro-nano structure on the surface; S6. Reduction: placing the wick into a reduction furnace for reduction treatment. The temperature of the reduction furnace is controlled at 400° C. to convert the hairy micro-nano structure obtained by oxidation into a more stable compound.
5. A method for preparing a catheter-like absorbent core, used for preparing the catheter-like absorbent core according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, powder filling, mixing fine copper powder with high temperature decomposable powder and putting them into a pre-designed mold cavity, vibrating the mold at high frequency to make the powder fully fill the mold cavity, and squeezing the mold to compact the powder; S2, sintering, placing the mold filled with powder into a high-temperature furnace, the temperature of the high-temperature furnace is controlled at 900℃ to 940℃, at high temperature, the contact surface of the material particles undergoes physical and chemical changes and combines with each other, the fine copper powder forms a tubular microchannel, the high-temperature decomposable powder evaporates and disappears after heating and forms a side pore profile; S3, demoulding, demoulding after cooling, and taking out the catheter-like liquid-absorbing core from the mold; S4, oxidation, placing the liquid absorbent core into an oxidation furnace for oxidation treatment, the temperature of the oxidation furnace is controlled at 500°C, and the oxidant reacts with the liquid absorbent core at high temperature to produce a hairy micro-nano structure on the surface; S5. Reduction: placing the wick into a reduction furnace for reduction treatment. The temperature of the reduction furnace is controlled at 400° C. to convert the hairy micro-nano structure obtained by oxidation into a more stable compound.
6. An ultra-thin heat spreader, characterized in that: It comprises an upper shell, a lower shell and a plurality of catheter-like liquid-absorbing cores as described in any one of claims 1 to 3; The top surfaces of the multiple catheter-like liquid-absorbing cores are connected to the upper shell, and the bottom surfaces are connected to a single-layer catheter-like liquid-absorbing core; the bottom surface of the single-layer catheter-like liquid-absorbing core is connected to the lower shell; Intervals are arranged between the plurality of imitation catheter liquid-absorbing cores to form steam channels.
7. The ultra-thin vapor chamber according to claim 6, characterized in that: The spacing between the catheter wicks is 1.5mm to 4mm.
Citation Information
Cited By
Composite wick, vapor chamber and heat pipe
CN120426797A